IMPACT OF SPRAYING MELATONIN, POTASSIUM, AND ZINC ON KUMQUAT FRUIT TRAITS AND SOME CHEMICAL CONCENTRATIONS - Hussein J. Al-Kinani; Ausama Y. Salih (The Iraqi Journal of Agricultural science)
This experiment was conducted at the Department of Horticulture and Landscape Engineering, College of Agricultural Engineering Sciences, University of Baghdad, during 2022 season to investigate the effect of spraying with melatonin, potassium sulfate, and organic zinc on the flowering and production stage, of 3-year old Kumquat saplings grafted onto lemon rootstock. The experiment was factorial within Randomized Completely Block Design using three replications. The factors of the experiment were foliar spraying with melatonin, potassium sulfate, and organic zinc. The treatments were applied at two times, spring and autumn. Each of the three factors independently influenced both the fruit characteristics and the concentration of chemical elements within the fruits. Melatonin application at a concentration of 20 mg.L-1 resulted in a remarkable improvement in fruit traits, specifically by increasing the number of fruits, fruit size, and fruit weight. This treatment also demonstrated a positive impact on the concentrations of various chemicals within the fruits, including TSS, total sugars, ascorbic acid, carotenoids, and phenols. Potassium sulfate applied at a concentration of 3000 mg.L-1 and organic zinc applied at a concentration of 1000 mg.L-1 exhibited the most pronounced effects on the same fruit traits that were positively influenced by melatonin.